Influence of Competitive Strategies on Firm Performance in the Telecommunication Industry: A Case Study of Telkom Kenya in Nakuru East Sub County - Chumba, Paul Kipterer; Chepkilot, Ronald; Tanui, John Kipkorir (World Journal of Innovative Research, 2019)
Firm performance of the telecommunication companies is thus important in Kenya's context. However, comparing the firm performance of Telkom Kenya Limited with other mobile phone service providers, Telkom Kenya Limited has performed relatively low compared to its peers as evidenced by data from communication authority of Kenya. Competitive strategies have been noted as key drivers of firm performance around the world. This study sought to examine the role of competitive strategies on the firm performance of Telkom Kenya. In particular, the study examined the influence of differentiation strategy and cost strategy on firm performance of Telkom in Nakuru. The study was guided byInstitutional Theory and Michael Porter Theory. This study utilized a correlational research design. The target population of this study is 56 Telkom Kenya staff involved in marketing, finance and operations aspects of the Telkom offices at Nakuru East Sub County. The study used the census method in selecting sample members. The sample size of the study is therefore 56 Telkom Kenya staff based in Nakuru East Sub County offices. The study used structured questionnaires for the purposes of the data collection process. A pilot study was undertaken in Naivasha offices of Telkom Kenya. The validity of the instrument in this study was examined using the content validity of the instrument. Reliability of the research instrument in this study was examined using the Cronbach alpha coefficient. Data was coded into the SPSS software in preparation for data analysis. The data from the questionnaire was analysed using descriptive and inferential statistics. The statistics to be undertaken include frequencies, chi-square, and linear regression analysis.The results of this study indicate that a positive statistical significance relationship existed between differentiation and firm performance. In respect to the influence of the cost strategy on the firm performance, the results indicated that there was a positive and statistically significant relationship between cost strategy and firm performance.The study recommended that the competitive strategies such as focus strategy, differentiation strategy and cost strategy should be implemented continuously by the organization. The study further recommends that Telkom Kenya as a firm should place its emphasis on cost strategy as it had the most influence on the firm performance at the organization followed by focus strategy, and differentiation strategy respectively.
FULL TEXT
Keywords: Competitive Strategies, Firm performance, Differentiation Strategy, Cost Leadership.